Charting digital governance: a bibliometric analysis of information and communication technology research in Nigeria's public administration using Scopus - Ishola, Abdulrasaq Ajadi; Maramura, Tafadzwa Clementine; Gumbo, Trynos (Frontiers in Sustainable Cities, 2025)
IntroductionThe increasing adoption of technology by developing nations' governments has sparked academic interest in Nigeria, particularly regarding its role in public service delivery.MethodsThis study conducts a bibliometric analysis of 128 Scopus-indexed publications on Information and Communication Technology (ICT) in Nigerian public administration using VOSviewer and Biblioshiny tools.ResultsThe analysis reveals that leading researchers from the University of Johannesburg, Obafemi Awolowo University, and the University of Ilorin dominate the field. Key publications appear in journals such as Electronic Library, Information Development, and Africa Journal of Science, Technology, Innovation and Development. Current research primarily focuses on e-governance adoption, implementation challenges, and success factors, with emerging interest in digital libraries, public value, and e-services.DiscussionThe study identifies critical research gaps, particularly in understanding digital governance's impact on vulnerable populations such as children, rural communities, the elderly, and people with disabilities. In addition, there is a need to develop context-appropriate indigenous technologies that incorporate emerging trends such as IoT, big data, and digital twins. The study recommends increased institutional support and funding for academic research to address these gaps and enhance the quality of ICT-public administration research in Nigeria.